Analisis Tahanan Kontak pada Pemisah (PMS) 150 kV Berdasarkan Hasil Pemeliharaan di PT. PLN (Persero) Gardu Induk Sutami - Soedjarwanto, Noer; Kenya Excellentia Kines; Saka Arif Aulia (Jurnal Teknik Ilmu dan Aplikasi, 2024)
The substation is a part of the electricity distribution system from consumer generators. To maintain the operation of the substation in optimal condition, maintenance or upkeep needs to be carried out in accordance with applicable maintenance standards. One of the equipment that requires routine maintenance at the main substation is the Separator (PMS). The disconnector (PMS) functions as protective equipment installed at the main substation and functions to disconnect and connect electrical power in a no-load condition. For this reason, maintenance needs to be carried out which aims to maintain the performance of the Separator. In this practical work report, tests were carried out on the knives or contacts on the Separator (PMS) to determine the contact resistance value. Next, this value is processed to determine the value of Power Loss, Electrical Energy Loss, and Electricity Costs and to determine whether or not it is necessary to repair the Separator (PMS). The results of the 150 kV Separator contact resistance (PMS) test in the Tarahan 1 Conductor bay of the Sutami Main Substation in the R, S and Contact Resistance phases are in the normal category because they meet the permitted standards, namely R <100 µΩ. This means that the Contact Resistance tested is still in good condition and the PMS does not require further repairs and the calculation results show that the largest electricity costs occur in Phase S when the injection current is 300A, amounting to Rp. 1,098,938 and the lowest electricity costs occur in Phase R when the injection current is 100A, amounting to Rp. 89,397.